Examining and Extending Advertising's Dual Mediation Hypothesis to a Branded Mobile Phone App. Issue 2 (2nd July 2016) - Ahmed, Rahnuma; Beard, Fred; Yoon, Doyle
ABSTRACT: Advertising's dual mediation hypothesis (DMH) is an important model predicting the relationships among antecedent variables and advertising outcomes. The results of the study reported here extend this theory to a mobile phone branded app. Structural equation modeling with data collected from 277 Millennial participants showed that the DMH was the best-fitting model for explaining attitude toward the app among four competing models. Furthermore, an extended DMH, with an "intention to continue using the app" construct, was found to offer a superior fit over four other extended models and a better model than the traditional DMH.